1949
DOI: 10.1042/bj0440591
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin and the oxygen uptake of leguminous root nodules

Abstract: HAEMOGLOBIN IN LEGUMINOUS ROOT NODULES 591 3. As reported by Virtanen (1945), haemoglobin could not be detected in nodules produced by ineffective strains of Rhizobium. The amount of haematin in such nodules, estimated as pyridine haemochromogen, was much less than that in effective nodules. 4. Effective and ineffective strains of Rhizobium grown in pure culture differ little in the ratios of haematin/cell nitrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1950
1950
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 5 publications
0
8
1
Order By: Relevance
“…Credit for the enthusiasm and recognition of the r6le of leghemoglobin in nitrogen fixation goes to Virtanen and colleagues (358,359,367,368). Commendation is becoming the Cambridge investigators (171,172,314,315) for refinements in technique and the development of microchemical and microspectroscopic methods showing the location, distribution and concentration of these pigments in the nodule. Chronological accounts of the progress in these studies are traced in several recent reports (314,362).…”
Section: Rhizobia As Infecting Agentsmentioning
confidence: 99%
“…Credit for the enthusiasm and recognition of the r6le of leghemoglobin in nitrogen fixation goes to Virtanen and colleagues (358,359,367,368). Commendation is becoming the Cambridge investigators (171,172,314,315) for refinements in technique and the development of microchemical and microspectroscopic methods showing the location, distribution and concentration of these pigments in the nodule. Chronological accounts of the progress in these studies are traced in several recent reports (314,362).…”
Section: Rhizobia As Infecting Agentsmentioning
confidence: 99%
“…1). The rate of initiation is not limiting in these polysomes, as (4,26), the presence of these two components may provide a cellular compartment where nitrogen fixation and respiration can be maintained optimally under low partial pressure of oxygen. Earlier attempts (5, 6) to localize Lb were based on indirect methods which led to the conclusion that Lb is localized inside the membrane sacs enclosing the bacteroids.…”
mentioning
confidence: 99%
“…Kubo (11) has shown that nodule "hemoglobins" stimulate the uptake of oxygen by bacteriods from soybean nodules. It is the opinion of Smith (12), however, that the stimulatory effect is indirect and does not involve hemoglobin in the electron transport process. In view of the observations of Kubo (11) an experiment was designed to test the effect of nodule "hemoglobins" on the rate of oxygen uptake by the particles from nodule Rhizobium.…”
Section: Methodsmentioning
confidence: 94%